PENGARUH KUALITAS PELAYANAN TERHADAP LOYALITAS KONSUMEN DENGAN KEPUASAN KONSUMEN SEBAGAI MEDIASI (Studi Kasus Pada Banaran Resto di Kampoeng Kopi Banaran Bawen, Kabupaten Semarang) - Ludfi Andri Permana, 10.05.51.0142; Kunartinah, Kunartinah (Students Journal of Economic and Management, 2014)
The purpose of the research is to explain the effects of service quality to customersâ loyalty and customersâ satisfaction as the mediation. The population of the research is the customers of Kampoeng Kopi Banaran, located at Jalan raya Bawen â Solo Km 1,5 Bawen, Semarang Regency with an average of 6,692 customers per a month. The sample of the research is 100 customers. The sampling technique uses purposive sampling (sampling with the goal). The types of the data and the data collection techniques use primary data. The analysis technique uses the instrument test, path analysis ,coefficient of determination, F - test, t - test and mediation mediation. The results show that : (1). service quality has significant positive effect on customersâ satisfaction. ( 2 ) . service quality has significant positive effect on consumersâ loyalty. (3). Customersâ satisfaction has a significant positive effect on consumersâ loyalty. (4). Quality of service and customersâ satisfaction affects customersâ loyalty. The influence of Quality of service and customersâ satisfaction to customersâ loyalty is 79.8%. (5). Customersâ satisfaction is a variable that mediates between service quality to customersâ loyalty, because the quality of service to customer loyalty the quality of service to customer loyalty influent customer satisfaction is bigger than the direct effect of service quality on customer loyalty indirectly.Keywords : Service Quality, Customer Satisfaction, Customer Loyalty